Disease‐Modifying Therapies and Coronavirus Disease 2019 Severity in Multiple Sclerosis. Issue 4 (9th February 2021) - Sormani, Maria P.; De Rossi, Nicola; Schiavetti, Irene; Carmisciano, Luca; Cordioli, Cinzia; Moiola, Lucia; Radaelli, Marta; Immovilli, Paolo; Capobianco, Marco; Trojano, Maria; Zaratin, Paola; Tedeschi, Gioacchino; et al.
Abstract : Objective: This study was undertaken to assess the impact of immunosuppressive and immunomodulatory therapies on the severity of coronavirus disease 2019 (COVID‐19) in people with multiple sclerosis (PwMS). Methods: We retrospectively collected data of PwMS with suspected or confirmed COVID‐19. All the patients had complete follow‐up to death or recovery. Severe COVID‐19 was defined by a 3‐level variable: mild disease not requiring hospitalization versus pneumonia or hospitalization versus intensive care unit (ICU) admission or death. We evaluated baseline characteristics and MS therapies associated with severe COVID‐19 by multivariate and propensity score (PS)‐weighted ordinal logistic models. Sensitivity analyses were run to confirm the results. Results: Of 844 PwMS with suspected (n = 565) or confirmed (n = 279) COVID‐19, 13 (1.54%) died; 11 of them were in a progressive MS phase, and 8 were without any therapy. Thirty‐eight (4.5%) were admitted to an ICU; 99 (11.7%) had radiologically documented pneumonia; 96 (11.4%) were hospitalized. After adjusting for region, age, sex, progressive MS course, Expanded Disability Status Scale, disease duration, body mass index, comorbidities, and recent methylprednisolone use, therapy with an anti‐CD20 agent (ocrelizumab or rituximab) was significantly associated (odds ratio [OR] = 2.37, 95% confidence interval [CI] = 1.18–4.74, p = 0.015) with increased risk of severe COVID‐19. Recent use (<1 month) of methylprednisolone was also associated with a worse outcome (OR = 5.24, 95% CI = 2.20–12.53, p = 0.001). Results were confirmed by the PS‐weighted analysis and by all the sensitivity analyses. Interpretation: This study showed an acceptable level of safety of therapies with a broad array of mechanisms of action. However, some specific elements of risk emerged. These will need to be considered while the COVID‐19 pandemic persists. ANN NEUROL 2021;89:780–789